The role of influencers’ credibility in shaping female students’ skincare purchase intentions - Polinar, Mark Anthony N. (Journal of Management, Economics, and Industrial Organization, 2025)
This study examined the influence of social media influencers’ credibility (attractiveness, trustworthiness, expertise, and attitude toward the brand) on shaping female students’ intentions to purchase endorsed skincare products. A descriptive-correlational study was employed to determine the degree of agreement between the parameters of social media influencers’ credibility and purchasing intention, and to explore the interplay of these variables. Responses from 385 female students were randomly selected using the Cochran sampling technique and gathered using an adapted survey questionnaire. The collected data were subsequently tallied, tabulated, and evaluated using a weighted mean and a Pearson correlation coefficient (r). The study illustrated that the female students agreed on all aspects of social media influencers’ credibility. Additionally, the interplay of variables revealed that trustworthiness (r = 0.169) and attitude towards the brand (r = 0.347) are correlated with purchasing intention; however, attractiveness and expertise are not correlated. This implies that social media influencers are perceived as trustworthy and have positive attitudes towards the brand, influencing female students’ purchase decisions for endorsed skincare products. These findings have practical implications for brand owners who are actively present on social media platforms, suggesting that partnering with trusted and reliable social media influencers can serve as a valuable marketing leverage in their business. However, these findings are limited to female senior high school students in Cebu City, Philippines.